Effects of Metformin and N-Acetylcysteine on Dyslipidemia in Streptozotocin-Induced Diabetic Rats - Novera Sohail Bajwa, Saveela Sadaqat, Wajahat Ullah Khan, Mehwish Mohsin, Mahak Memon, M. Waqar Aslam, Rizwan Masud (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Diabetes is a chronic health issue globally that has a high incidence. Aim: To see the effects of metformin and N-acetylcysteine on dyslipidemia in streptozotocin-induced diabetic rats. Study Design: Randomized controlled trial. Methodology: A total of 25 rats were divided into 05 equal groups. Diabetes was induced into rats by streptozotocin (35 mg/kg) single doze (i.p). Rats having blood sugar >300 mg/dl after 48hrs were considered as diabetic. Negative and positive control groups were fed on standard diet. Treatment groups were given Metformin, N-acetylcysteine and combination of Metformin and N-acetylcysteine respectively for 4 weeks. Groups were compared for lipid profile thus efficacy of treatment given was evaluated. SPSS 25.0 was used to analyze the whole data. The difference between all the groups was analyzed using One-Way Analysis of Variance (ANOVA). Results: There was significant improvement in a treatment group that received both Metformin plus N-acetylcysteine while other treatment groups had little improvement. Conclusion: It was concluded that dyslipidemia was significantly reduced by use of N-acetylcysteine in combination with metformin among diabetic rats.